'Trying to find information is like hating yourself every day': The collision of electronic information systems in transition with patients in transition. (September 2013) - McMurray, Josephine; Hicks, Elisabeth; Johnson, Helen; Elliott, Jacobi; Byrne, Kerry; Stolee, Paul
The consequences of parallel paper and electronic medical records (EMR) and their impact on informational continuity are examined. An interdisciplinary team conducted a multi-site, ethnographic field study and retrospective documentation review from January 2010 to December 2010. Three case studies from the sample of older patients with hip fractures who were transitioning across care settings were selected for examination. Analysis of data from interviews with care providers in each setting, field observation notes, and reviews of medical records yielded two themes. First, the lack of interoperability between electronic information systems has complicated, not eased providers' ability to communicate with others. Second, rather than transforming the system, digital records have sustained health care's 'culture of documentation'. While some information is more accessible and communications streamlined, parallel paper and electronic systems have added to front line providers' burden, not lessened it. Implementation of truly interoperable electronic health information systems need to be expedited to improve care continuity for patients with complex health-care needs, such as older patients with hip fractures.